Acute Pulmonary Exacerbations in Cystic Fibrosis - Goss, Christopher H. (Seminars in Respiratory and Critical Care Medicine, 2019)
With the improving survival of cystic fibrosis (CF) patients and the advent of highly effective cystic fibrosis transmembrane conductance regulator therapy, the clinical spectrum of this complex multisystem disease continues to evolve. One of the most important clinical events for patients with CF in the course of this disease is an acute pulmonary exacerbation. Clinical and microbial epidemiology studies of CF pulmonary exacerbations continue to provide important insight into the disease course, prognosis, and complications. This work has now led to a number of large scale clinical trials with the goal of improving the treatment paradigm for CF pulmonary exacerbation. The primary goal of this review is to provide a summary of the pathophysiology, the clinical epidemiology, microbial epidemiology, outcome and the treatment of CF pulmonary exacerbation.
Keywords: FEV1; respiratory symptoms; pulmonary exacerbation; cystic fibrosis; treatment duration